A practical and efficient reliability-based design optimization method for rock tunnel support. (September 2022) - Zhao, Hongbo
Highlights: Developed a practical, efficient reliability-based design optimization approach. Determined the reliability index using the first two moments based on the MDRM model. Approximated the engineering response using HDMR. Avoided extensive computations and improved efficiency significantly. Verified and illustrate the developed approach using a rock tunnel. Abstract: Uncertainty is an intrinsic feature in rock mechanics and engineering, and uncertainty analysis is an important challenge to stability analysis, design, and construction in the context of rock engineering. In this study, a reliability-based design optimization (RBDO) approach is developed to determine the design parameters for engineering by combining the moment method and high-dimensional model representation (HDMR). Multiplicative dimensional reduction (MDRM) is used to approximate and determine the statistical moment of a rock tunnel response. The first-order second moment is used to estimate the reliability index based on the MDRM model. The complex, high-dimensional, and nonlinear response of the engineering structure is determined by HDMR. Microsoft Solver is used as optimization technology for the RBDO. The proposed approach was applied to a circular tunnel with rock bolts and the procedure was examined using a Monte Carlo simulation. The results show that the proposed method can determine the reliability index and design variables in the RBDO, and provide a simple and feasible way to consider uncertainties in design, stability analysis, and construction in rock engineering.